ADSORPTION OF HEAVY METAL USING SLUDGE ACTIVATED CARBON DERIVED FROM SLUDGE - Mohammad Jamin, Wan Izzudin (Universiti Teknologi PETRONAS, 2017)
The amount of sludge produced by the domestic and sewage company is about 5.3 million3 per year and most of the sludge are being wasted in an unused landfill. This study proposed dry activated sludge as low-cost adsorbents for the Zn(II) from the wastewater. It is focused on the adsorption of Zn(II) by sludge biomass-based activated carbon which will be conducting using batch tests. The effect of contact time, initial metal ions concentration and adsorbent dosage on the removal of Zn(II) from the synthetically produced wastewater were investigated. The removal efficiency was found to have relations with the initial Zn (II) concentration, contact time as well as adsorbent dosages of the adsorbents. The adsorption kinetics of the heavy metal ion, Zn(II) by SAC adsorbent were found to follow pseudo-second order kinetic models indicates that the experiment undergone chemisorption process.